Про наближений аналіз еволюції плоскої поздовжньої гіперпружної хвилі - Рущицький, Я.Я. (Доповіді НАН України, 2019)
Описано та прокоментовано деcять варіантів (відомих і нових) наближеного аналізу еволюції плоскої поздовжньої хвилі, яка поширюється в нелінійно гіперпружному середовищі. Показано, що кожен варіант дає відповідь на певний аспект в студії еволюції хвилі. Акцентовано увагу на подібності і відмінності в отриманих результатах. Three approaches (methods) are used to analyze the evolution of a plane longitudinal wave that propagates in a nonlinear hyperelastic medium — method of successive approximations, method of slowly varying amplitudes, and method of restriction on the displacement gradient. The evolution is understood as changing the initial wave profile during the propagation of a wave in the nonlinear elastic medium. Ten variants (known and new) of an approximate analysis of the evolution of a plane longitudinal wave propagating in an hyperelastic medium are described and commented. It is shown that each variant gives answer on some aspect in studying the wave evolution. An attention is drawn to the similarity and the difference in the results of analysis. Описаны и прокомментированы деcять вариантов (известных и новых) приближенного анализа эволюции плоской продольной волны, распространяющейся в нелинейно гиперупругой среде. Показано, що каждый вариант дает ответ на некоторый аспект в изучении эволюции волны. Акцентировано внимание на подобии и отличии в полученных результатах.